Role of Nuclear Imaging in Cardiac Amyloidosis Management: Clinical Evidence and Review of Literature - Frantellizzi, Viviana; Cosma, Laura; Pani, Arianna; Pontico, Mariano; Conte, Miriam; De Angelis, Cristina; De Vincentis, Giuseppe (Current Medical Imaging, 2020)
Cardiac amyloidosis (CA) is an infiltrative disease characterized by the extracellular deposition of fibrils, amyloid, in the heart. The vast majority of patients with CA has one of two types between transthyretin amyloid (ATTR) and immunoglobulin light chain associated amyloid (AL), that have different prognosis and therapeutic options. CA is often underdiagnosed. The histological analysis of endomyocardial tissue is the gold standard for the diagnosis, although it has its limitations due to its invasive nature. Nuclear medicine now plays a key role in the early and accurate diagnosis of this disease, and in the ability to distinguish between the two forms. Recent several studies support the potential advantage of bone-seeking radionuclides as a screening technique for the most common types of amyloidosis, in particular ATTR form. This review presents noninvasive modalities to diagnose CA and focuses on the radionuclide imaging techniques (bone-seeking agents scintigraphy, cardiac sympathetic innervation and positron emission tomography studies) available to visualize myocardial amyloid involvement. Furthermore, we report the case of an 83-year old male with a history of prostate cancer, carcinoma of the cecum and kidney cancer, submitted to bone scan to detect bone metastasis, that revealed a myocardial uptake of 99mTC-HMPD suggestive of ATTR CA. An accurate and early diagnosis of CA able to distinguish beyween AL and ATTR CA combined to the improving therapies could improve the survival of patients with this disease.
Keywords: PET radiotracers